Standardisation of Vitexin and Isovitexin in Ficus deltoidea var. Kunstleri (FDK) Extract and Anti-Hyperlipidaemic Properties of FDK Hydrogel in High Cholesterol Diet-Induced Early and Established Atherosclerosis Rabbits - Ramli, Faiqah Binti; Mohd Ariff, Amirah; Kasim, Alicezah Mohd; Nawawi, Hapizah; Omar, Effat; Abd. Muid, Suhaila (Trends in Sciences, 2025)
Hyperlipidaemia is a major risk factor for cardiovascular disease (CVD) due to its role in forming atherosclerotic plaques. Finding natural products with anti-hyperlipidaemic properties is important for preventing atherosclerosis. Ficus deltoidea var kunstleri extract (FDK) is traditionally used to regulate blood glucose and blood pressure, however its effect on lowering lipid is scarce. Previous study showed neutral effects of FDK extract on lipids. Hydrogel delivery is commonly used to enhance absorption of active compounds therefore enhancing their therapeutic effect. This study aimed to develop a FDK hydrogel from standardised FDK extract and evaluate its effectiveness in lowering lipids and atherogenic index (AI) in high cholesterol (HC)-induced-early and established atherosclerosis rabbits. Standardised FDK extract against vitexin and isovitexin was produced according to a standard guideline using Liquid chromatography-tandem mass spectrometry (LCMS/MS) method prior to the preparation of FDK hydrogel (FDKH). Forty-rabbits were fed with 1 % high cholesterol diet for 4 and 8 weeks to induce early and established atherosclerosis, respectively. Each group was subdivided into 4 intervention arms: 1) FDKH 125 mg/kg; 2) FDKH 250 mg/kg; 3) Simvastatin 5 mg/kg; and 5) placebo for 8 weeks. Lipid profile and atherogenic index (AI) were measured at the baseline (B0), post-HC diet and post-treatment in both early and established atherosclerosis rabbits. Quantitative analysis of FDK using LC-MS/QQQ reveals the presence of 3.5 ± 0.04 mg/g of vitexin and 3.1 ± 0.8 mg/g isovitexin, respectively. In the early atherosclerotic group, at week 12, all treatment groups showed significant reductions in total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG) compared to week 4. The reductions varied by treatment type. FDKH 250 mg/kg resulted in the highest reductions in TC and LDL-C, followed by FDKH 125 mg/kg and simvastatin, which is still higher than placebo. Interestingly, simvastatin led to the greatest reduction in TG, followed by FDKH 125 mg/kg and FDKH 250 mg/kg. In the established atherosclerotic group, FDKH 250 mg/kg again demonstrated the highest reductions in TC, LDL-C and TG levels, confirming its efficacy in more advanced stages of atherosclerosis. Both FDKH dosages significantly improved AI compared to the placebo, with FDKH 250 mg/kg showing the lowest AI value. These findings suggest that FDKH, particularly at the 250 mg/kg dosage, is highly effective in reducing lipid levels and improving AI, indicating its potential as a potent alternative to traditional treatments like simvastatin. Further clinical trials are warranted to confirm these results and explore the long-term effects and safety of FDKH in humans. In conclusion, FDKH have significant potential to mitigate serum lipid and atherogenesis in both early and established atherosclerosis rabbits. This advancement represents a promising adjunct treatment option, offering a natural and effective solution for hyperlipidaemia. HIGHLIGHTS Ficus deltoidea var kunstleri (FDK) extract was successfully standardised using a validated LC-MS/QQQ method against 2 major bioactive components, vitexin and isovitexin. Treatment with FDK hydrogel (FDKH) led to a significant reduction of TC, LDL and TG and atherogenic index in high cholesterol-induced-early and established atherosclerosis rabbits. FDKH have significant potential to mitigate serum lipid and atherogenesis in both early and established atherosclerosis rabbits. This study suggests a promising adjunct treatment option of FDKH, offering a natural and effective solution for hyperlipidaemia. GRAPHICAL ABSTRACT